ANALISIS EFEKTIVITAS DAN EFISIENSI KINERJA KEUANGAN PADA BADAN KEPEGAWAIAN NEGARA TAHUN 2018-2021 - Yuanne Gabrila Sriyanto; Angelina Yunita Munte; Risma Wira Baharata (Politeknik Negeri Ambon, 2023)
This study aims to analyze the financial performance of the Republic of Indonesia Civil Service Agency. The observation period is 2018-2021. The data used in this study are secondary data, namely financial reports and performance reports of the Indonesian Civil Service Agency. The research results show that the financial performance of the Republic of Indonesia State Personnel Agency has been effective and there have been fluctuations in financial performance seen from the efficiency ratio of its performance.